LANGUAGE LEARNING STRATEGIES: GENDER AND PROFICIENCY - Idham Syahputra (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2014)
This study described and examined on the current English language learning strategies used by Indonesian Students English Education Department enrolled at State Islamic University of Sultan SyarifKasim Riau in Indonesia. The subjects of the study were (99) male and female students still studying for their Undergraduate degree in English Education Department. The study investigates the frequency of strategies use among these students according to gender and proficiency variables. Proficiency is reflected by students’ learning level (i.e., sophomore, junior, senior), self-reported proficiency in English (i.e., the students’ university average in English courses) and language self-efficacy (i.e,. how good the students perceived themselves as English learners). The collecting data used Questionnaire adopted from Oxford (1990a), Mohammad Amin Embi (1996) danPolitzer (1993), interview lecturers about the language learning strategies used by students. The results of this study showed that State Islamic University of Sultan SyarifKasim, English Education Department used learning strategies with high to medium frequency, and that the highest rank (79.6%) was for Metacognitive strategies while the lowest (63%) was for compensation strategies and the others used cognitive, memory, affective and social. In general, the results showed that gender and proficiency had no significant differences on the use of strategies. Based on these findings, the researcher recommends that more training should be given in using Cognitive, Memory, Affective, social and Compensation strategies by embedding them into regular classroom activities or teaching and learning process